2014
DOI: 10.1111/jsap.12294
|View full text |Cite
|
Sign up to set email alerts
|

Vertical forces assessment according to radiographic hip grade in German shepherd dogs

Abstract: Mean peak vertical force was lower in dogs with severe hip dysplasia compared with mildly dysplastic dogs. These results suggest that hip dysplasia degree can affect lameness severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 32 publications
2
20
1
2
Order By: Relevance
“…Additionally, this improvement at week 2 in the control group was not reflected in force plate data. Force plate data have been reported to be an unbiased outcome measure, which strengthens the results of our study. This improvement in some owner‐observed pain and lameness scores for the placebo control injection was unexpected.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, this improvement at week 2 in the control group was not reflected in force plate data. Force plate data have been reported to be an unbiased outcome measure, which strengthens the results of our study. This improvement in some owner‐observed pain and lameness scores for the placebo control injection was unexpected.…”
Section: Discussionsupporting
confidence: 90%
“…The objective measures of lameness used in our study were PVF and VI. These are commonly used components of gait analysis in veterinary medicine . Peak vertical force is dependent on gait velocity; however, our data showed that there was no significant difference in gait velocity between time points and gait velocity was not significantly different between control and treated dogs.…”
Section: Discussioncontrasting
confidence: 67%
“…Nonetheless, objective data are limited and contradict the hypothesis that such compounds would promote improved weight bearing (Moreau et al, 2003). The lack of scientific evidence supporting beneficial effects of CS-GLU supplementation has been repeatedly emphasized (Aragon et al, 2007;Sanderson et al, 2009;Vandeweerd et al, 2012). This study set out to obtain quantitative weight bearing data from osteoarthritic dogs undergoing treatment with CS-GLU, given the unreliable nature of visual analogue scales and other subjective methods employed in lameness evaluation of dogs with OA (Hielm-Björkman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Chondroprotectors are widely used for conservative treatment of canine OA. Although moderate pain relief can be achieved, scientific evidences of effects in dogs, cats and horses are weak (Aragon et al, 2007;Sanderson et al, 2009;Vandeweerd et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation